Understanding Chinese Governance by Critiquing ‘Religion’ - Gao, Zhe (Method & theory in the study of religion, 2024)
As an indirect response to Galen Watts and Sharday Mosurinjohn’s “Can Critical Religion Play by Its Own Rules?” this article aims to explicate what ‘critical religion’ as a distinct theoretical framework means for the author in terms of how it has provided them a critical framework for understanding the history of China, especially its transition of self-identification from tianxia (天下, all under Heaven) to a secular nation state, and some of its pressing ‘religious’ issues today. Upon the identification of a postcolonial condition in modern China where the indigenous elite have uncritically accepted ‘religion’ and other interdependently arisen modern categories, not only will the differentiation between ‘Chinese religion’ and ‘Chinese politics’ be demonstrated as an illusion, but ‘negotiating religion’ will be proved by means of two case studies as a more adequate approach to understanding the governance by the Chinese Communist Party in contemporary China.